Substrate‐analogue complex structure of Mycobacterium tuberculosis decaprenyl diphosphate synthase. Issue 4 (5th April 2019) - Ko, Tzu-Ping; Xiao, Xiansha; Guo, Rey-Ting; Huang, Jian-Wen; Liu, Weidong; Chen, Chun-Chi
Abstract : The structure of a complex of Mycobacterium tuberculosis decaprenyl diphosphate synthase with geranyl S ‐thiodiphosphate and isopentenyl S ‐thiodiphosphate was refined to 1.55 Å resolution. It not only shows the magnesium‐coordinated configuration for catalysis but also suggests a pathway for product translocation as well as a direction for inhibitor design. Abstract : Decaprenyl diphosphate synthase from Mycobacterium tuberculosis ( Mt DPPS, also known as Rv2361c) catalyzes the consecutive elongation of ω, E, Z ‐farnesyl diphosphate ( EZ ‐FPP) by seven isoprene units by forming new cis double bonds. The protein folds into a butterfly‐like homodimer like most other cis ‐type prenyltransferases. The starting allylic substrate EZ ‐FPP is bound to the S1 site and the homoallylic substrate to be incorporated, isopentenyl diphosphate, is bound to the S2 site. Here, a 1.55 Å resolution structure of Mt DPPS in complex with the substrate analogues geranyl S ‐thiodiphosphate (GSPP) and isopentenyl S ‐thiodiphosphate bound to their respective sites in one subunit clearly shows the active‐site configuration and the magnesium‐coordinated geometry for catalysis. The ligand‐binding mode of GSPP in the other subunit indicates a possible pathway of product translocation from the S2 site to the S1 site, as required for the next step of the reaction. The preferred binding of negatively charged effectors to the S1 site also suggests a promising direction for inhibitor design.